Penggunaan Electrical Impedance Spectroscopy (EIS) untuk Mengidentifikasi Kerusakan Mekanis pada Buah Apel - Sugianti, Cicih; Maktub, Zana Azalia (abe.fp.unila.ac.id, 2024)
Mechanical damage is a common issue that affects the quality and marketability of apples during postharvest handling and storage. This study aims to identify mechanical damage in apples using Electrical Impedance Spectroscopy (EIS) as a non-destructive evaluation method. EIS measurements were conducted to analyze the electrical properties of both damaged and intact apples. Results showed that damaged apples exhibited lower extracellular resistance (7.8 kΩ) compared to intact apples (44.67 kΩ), indicating increased electrolyte leakage due to cell membrane disruption. Cole-Cole plot analysis further revealed significant differences in the impedance characteristics of apples, reflecting the extent of tissue damage. These findings demonstrate that EIS effectively detects mechanical damage by assessing changes in cellular integrity. The method provides a rapid, accurate, and non-invasive approach for quality control in apple handling and storage processes. Keywords: Apple, Cell Membrane Integrity, Extracellular Resistance, Electrical Impedance Spectroscopy (EIS), Mechanical Damage.